1991
DOI: 10.2527/1991.6972904x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the influence of dietary vitamin E on sows and offspring in three parities: reproductive performance, tissue tocopherol, and effects on progeny

Abstract: Sixty crossbred (Yorkshire-Hampshire X Duroc) gilts were fed one of four corn-soybean meal diets fortified with .3 ppm Se and 0, 16, 33, or 66 IU of DL-alpha-tocopheryl acetate/kg. The study was conducted over a three-parity period to evaluate sow reproductive performance and the vitamin E tissue status of both sows and progeny at various time periods postcoitum and(or) postpartum. The basal diet averaged 8.4 mg of alpha-tocopherol/kg and .38 ppm of Se. Although litter size at birth was lowest (P less than .15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
54
3
2

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 4 publications
15
54
3
2
Order By: Relevance
“…According to Lauridsen et al (2002), piglet fat and the brain were the only tissues in which α-tocopherol concentrations increased from 7 to 21 days of lactation when mothers were supplemented. Other investigators have found a tendency for greater vitamin E concentration in piglets of sucking sows receiving high levels of DL-α-tocopheryl acetate (Mahan, 1991;Hiridoglou et al, 1993;Pinelli-Saavedra et al, 2008) or D-α-tocopheryl acetate (Mahan et al, 2000) because of the high absorption from sow's milk. The predominant importance of sow over piglet supplementation was observed when α-tocopherol stereoisomers in the muscle at 39 day of age were quantified (Table 4).…”
Section: Resultsmentioning
confidence: 96%
“…According to Lauridsen et al (2002), piglet fat and the brain were the only tissues in which α-tocopherol concentrations increased from 7 to 21 days of lactation when mothers were supplemented. Other investigators have found a tendency for greater vitamin E concentration in piglets of sucking sows receiving high levels of DL-α-tocopheryl acetate (Mahan, 1991;Hiridoglou et al, 1993;Pinelli-Saavedra et al, 2008) or D-α-tocopheryl acetate (Mahan et al, 2000) because of the high absorption from sow's milk. The predominant importance of sow over piglet supplementation was observed when α-tocopherol stereoisomers in the muscle at 39 day of age were quantified (Table 4).…”
Section: Resultsmentioning
confidence: 96%
“…In addition to being stimulated by antioxidants, the increase in plasma values of vitamins A and E is also influenced by the integration of these vitamins in the diet (Mahan, 1991;Hidiroglou et al, 1993;Njeru et al, 1994;Corino et al, 1999;Oriani et al, 2001;Lauridsen et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Oils in sow diets during early-to-mid gestation established; bearing in mind that supplementation was given during the first 60 days of gestation only, there are a number of ways in which the increased litter size may be explained: (i) the fatty acid profile of the diet may alter maternal endocrine status (Hornstra and Stegan, 1989), which in turn may affect embryonic survival and the efficiency of placental development; (ii) palm oil is a rich source of the anti-oxidants b-carotene and vitamin E (Duran, 2002;Edem, 2002) and increased intake of vitamin E has previously been linked to increased litter size in pigs (Mahan, 1991;Pinelli-Saavedra, 2003); (iii) palm oil supplementation may result in glucose sparing in the mother, allowing greater glucose availability for the placenta/foetuses as seen in humans and rats (Kim et al, 1995;Jaquier, 1998;Melanson et al, 1999); (iv) palmitic acid (16:0), primarily from the diet during the first half of gestation, but also from lipolysis of maternal adipose tissue during late pregnancy, may be converted into ketones and improve energy availability to the developing placenta/foetuses (Secombe et al, 1977;Shambaugh, 1985) resulting in better piglet metabolic status at birth (Newcomb et al, 1991;Azain, 1993); and (v) the fatty acids present in palm oil may be …”
Section: --mentioning
confidence: 99%